Association of Symphyseal Morphology with Lower Incisor Inclination in Sagittal and Vertical Growth Patterns - Waheed Gul Shaikh, Nosheen Khawar, Asha Devi, Batool Sajjad, Syed Ahmed Omer, Marium Azfar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The mandibular symphysis is the bodily carnal part of the mandible that consist of alveolar and cortical bones. The mandibular symphysis has different parts like chin, or mentum that consist of unique features of modern humans. Objective: The study aimed to explore the correlation of lower incisor inclination growth pattern with the symphyseal morphology. Study design: It is a retrospective study conducted at Orthodontic Department, Shahida Islam Dental College, Lodhran and Fatima Jinnah Dental College, Karachi for the duration of six months from February 2022 to July 2022. Material and Methods: The correlation between all parameters was studied by ANOVA and other statistical analysis were also performed. The study approval was taken from the review board and ethical committee of the hospital. A total of 18 patients participated in this study. The patients were classified according to the facial category i.e. long, normal, and short. Class I comprises 8 patients and class III comprises 10 patients. Results: An increased value was observed in the case of class I with vertical growth patterns while the value decreased in the case of class III. Three different types of incisor inclinations were observed that is over jet positive, over jet negative, and edge to edge. Conclusion: From this study, it is predicted that a correlation exists between vertical growth patterns and sagittal growth patterns for the inclination in incisors. The height and width of the symphysis and facial patterns are also related to vertical growth patterns and indirectly affect the inclination of incisors. High angle facials have thin and long symphysis, while low angle facials have thick and short symphysis. Keywords: short symphysis, soft tissue and growth dimension.